Insomniacs after school. 1 - Ojiro, Makoto, 1982- (Viz signature., 2023)
"Unable to sleep at night, Ganta Nakami is cranky in class and unpopular with his classmates. He discovers that the school observatory, once used by the now-defunct astronomy club, may be the perfect place for a nap--but he's not along. Fellow insomniac Isaki Magari is willing to share the observatory with Nakami, and a friendship between the two begins as they bond over the most unlikely things. Dark rumors about what befell the members of the astronomy club keep people away from the school observatory, and that's what makes it the perfect sanctuary for Nakami and Magari to get some much-needed rest. Unfortunately, the school faculty can't allow its unsanctioned use. But if there were a new astronomy club, maybe these two insomniacs oculd have a place to call home!" --